2015
DOI: 10.1002/ejoc.201501309
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrochemical Properties of Anthraquinone Imine Based Dyes for Dye‐Sensitized Solar Cells

Abstract: A number of anthraquinone imines (1-3, 5-8) and an anthrone diamine (4) have been synthesized by the condensation of 9,9-dimethoxy-10-anthrone derivatives (13, 18, and 23) with different primary aromatic amines and, in the case of benzoacridinone 7, by a subsequent photoinduced 6π electrocyclization. All the compounds were fully characterized by UV/ Vis spectroscopy, cyclic voltammetry, and X-ray diffraction. The XRD analyses proved that the preferred tautomers of 1, 3, and 5 have the 9-amino-1,10-anthraquinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Currently, a lot of new imines with various symmetries are synthesized to be used as thermal, biological or liquid crystalline materials [5,6,7,8]. Moreover, some imines are tested in organic devices, such as solar cells [9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a lot of new imines with various symmetries are synthesized to be used as thermal, biological or liquid crystalline materials [5,6,7,8]. Moreover, some imines are tested in organic devices, such as solar cells [9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The latter can be achieved by incorporating different polar functional groups in the structure of sensitizer (as carboxylic acid, amines, ketones, among others). Prinzisky et al studied the performance of a hydroxy-anthraquinone imine as a dye for DSSCs [ 51 ], where the hydroxyl and imine groups acting anchoring the molecule to the TiO 2 semiconductor surface. Recently, Sreeja and Pesala studied the performance of natural dyes indigo, lawsone, and betanin as co-sensitizer for solar cells [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…As part of their research on anthraquinone imine dyes for DSSCs, Sundermeyer and co-workers reported in 2016 a four-step synthesis of benzoacridinone 191.3 ( Scheme 191 ). 371 The requisite precursor 191.1 had to be obtained via a monoacetal intermediate, to avoid selectivity problems. 191.1 was then photolyzed in a Mallory-type reaction, yielding 191.3 .…”
Section: Phenalenoidsmentioning
confidence: 99%